Systemic treatment of HER2+ metastatic breast cancer: Clinical conundrums and future perspectives. (June 2014) - De Boer, Richard; Beith, Jane; Chirgwin, Jacquie; Chua, Sue; Colosimo, Maree; Francis, Prudence; Green, Michael; Pittman, Ken; White, Michelle; Wilcken, Nicholas; Zdenkowski, Nicholas; Bell, Richard
Abstract: Improvements in the treatment of metastatic HER2‐positive breast cancer constitute one of the great advances in breast cancer medicine of the last generation. From being a highly aggressive fatal condition, the use of anti‐HER2‐targeted therapies, in particular trastuzumab, has led to significant improvements in disease outcomes. There are reports of increasing numbers of patients alive and well more than 5 years from diagnosis of metastatic disease. Nevertheless, there remain many complex and clinically difficult scenarios where there is little in the way of randomized evidence or published guidelines to guide decision making. As a companion piece to our review of HER2‐targeted therapies in the metastatic setting, we decided to focus on a series of clinical scenarios that fell outside of the standard trial‐based settings and where opinions and guidance from experienced clinicians and experts in the field would be considered useful to help develop safe and effective treatment strategies. The following eight cases were put forward by our panel of experts, voted on by their peers to select the most relevant and interesting cases, and the discussions worked on by teams of two followed by review and commentary by another team of two.